Modeling Uncertainty in Wave Loading on a Jacket Offshore Structure - Pattipawaej, Olga (Jurnal Teknik Sipil, 2006)
The objective of this study is to model uncertainties inherent in random wave excitation of steel jacket offshore structure. A probabilistic finite element method is used as the basis for addressing the uncertainties. To assess the performance of the method, comparison of the prediction model addressing various uncertainties in the problem will be made with deterministic predictions.